Systemic Immune Dyshomeostasis Model and Pathways in Alzheimer’s Disease - Talwar, Puneet; Kushwaha, Suman; Gupta, Renu; Agarwal, Rachna (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) still remains an enigma for researchers and clinicians. The onset of AD is insidious, gradually progressive and multifactorial with recent accumulated scientific evidences suggesting that the pathological changes resemble the autoimmune driven self-sustaining inflammatory process as a result of prolonged oxidative stress and immune dyshomeostasis. Apart from aging, various other factors mainly environmental, lifestyle, and neuroendocrine affect the immune system as the human beings are vulnerable to polymicrobial infections and chronic stress at any time of life. Here, we provide cross-talk among “trigger insults/inflammatory stimulus” i.e. polymicrobial infection, chronic stress, pro-inflammatory diet and cholinergic signaling to put forward “Systemic Immune Dyshomeostasis” model as to connect the events leading to AD development and progression. Our model implicates altered cholinergic signaling and suggests the pathological stages with various modifiable risk factors and triggers at different chronological age and stage of cognitive decline. The search of specific autoantibodies for AD which may serve as the suitable blood/CSF biomarkers should be actively pursued for the early diagnosis of AD. The preventive and therapeutic strategies should be directed towards maintaining the normal functioning of immune system throughout the life span and specific modulation of the immune responses in the brain respectively.